The Effect of Price Perception, Location, and Service Quality on Indomaret Customer Loyalty in Surakarta with Customer Satisfaction as a Mediating Variable - Garnisa Febriantika Chaterin Nastiti; Edy Purwo Saputro (Jurnal Economic Resource, 2026)
This experiment uses customer satisfaction as a mediating variable to examine how perceptions of cost, spot, and service quality affect customers at Indomaret in Surakarta. The study uses a quantitative method, drawing on data from questionnaires administered to 143 Indomaret customers in Surakarta. Purposive sampling was employed, and SmartPLS 4.0 was used to analyze the data using the Partial Least Squares (PLS) approach. The outcomes showed that while the location variable had no apparent impact on customer satisfaction, price perception, and service quality had a significant positive correlation. Furthermore, customer loyalty is positively and dramatically influenced by price perception, but location and service quality do not have a noticeable effect. Customer loyalty has been proven to be positively and significantly influenced by customer satisfaction. According to the R2 values for customer satisfaction and consumer loyalty (0.740 and 0.538, respectively), this experimental model has a strong and moderate level of viability. Given that customer satisfaction is the primary mediator in this relationship, our findings highlight the importance of price perception and service quality in promoting customer satisfaction and loyalty at Indomaret in Surakarta.